2011
DOI: 10.1002/ajim.21014
|View full text |Cite
|
Sign up to set email alerts
|

Coal mining is associated with lung cancer risk in Xuanwei, China

Abstract: Background Xuanwei, China, experiences some of the highest rates of lung cancer in China. While lung cancer risk has been linked to the household use of bituminous coal, no study has comprehensively evaluated the risk of lung cancer associated with the mining of this coal in Xuanwei. In Xuanwei, coal is typically extracted from underground mines, without ventilation, and transported to the surface using carts powered by manpower or electricity. Methods We evaluated the risk of lung cancer and working as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…Elevated lung cancer risks among coal miners were also observed in other case-control studies [eg (9)], although results did not reach the level of statistical significance in all these studies (11). By contrast, a hospital-based case-control study found no excess lung cancer risk among Dutch coal miners (12) in line with a case-control study nested into four industrial cohorts (10).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Elevated lung cancer risks among coal miners were also observed in other case-control studies [eg (9)], although results did not reach the level of statistical significance in all these studies (11). By contrast, a hospital-based case-control study found no excess lung cancer risk among Dutch coal miners (12) in line with a case-control study nested into four industrial cohorts (10).…”
Section: Discussionmentioning
confidence: 44%
“…Since then, epidemiological studies have reported mixed results on lung cancer among coal miners (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), with extended follow-ups of cohort studies among British and US coal miners recently suggesting a positive association. However, exposure-specific results for coal dust and silica were not coherent between the two studies.…”
mentioning
confidence: 99%
“…The proportion of people using solid fuel in China has decreased significantly from 64% in 1990, to 46% in 2010 171. However, in rural China, about two-thirds of people still use solid fuels, particularly coal, as their main source of energy for cooking and heating 172,178. In China, people use mainly two types of coal, predominantly smoky coal (bituminous coal), but also non-smoky or smokeless coal (anthracite).…”
Section: Lung Cancer and Upper Airway Cancersmentioning
confidence: 99%
“…There is a major overlap of emission products from incomplete combustion of coal and wood 175. Several studies have reported differences in types of coal on the basis of their geographical location (where mined) in China and also differences in the types of emission products such as the volatility levels of benzene and formaldehyde, which vary the carcinogenicity 172,178,181. For example, smoky coal is predominantly used in the southern regions of China and tends to have increased polycyclic aromatic hydrocarbons, silica, nickel, and arsenic contents and thus has higher carcinogenic potential than do different types of coal such as anthracite 172…”
Section: Lung Cancer and Upper Airway Cancersmentioning
confidence: 99%
“…Um estudo do tipo coorte realizado nos EUA com trabalhadores aeroespaciais encontrou um risco aumentado no desenvolvimento de câncer de pulmão quando expostos a óleos minerais 43 . Um aumento no risco de câncer de pulmão também pode ser observado, segundo alguns estudos, em trabalhadores de minas de carvão 44,45 e de minas de urânio 46 . Esse aumento no risco de câncer de pulmão também pode ser constatado em trabalhadores expostos ao radônio 47,48 , à fumaça produzida pelo forno de coque 41 , ao cloreto de vinila 49 e à combustão de diesel 50 .…”
Section: Câncer De Pulmão E Mesoteliomaunclassified